Antimicrobial Sulfated Glycans: Structure and Function - H. Pomin, Vitor (Current Topics in Medicinal Chemistry, 2017)
Owing to their inherent structural features, certain sulfated glycans isolated from terrestrial or marine mammals or invertebrates, can exert therapeutic properties against infections caused by pathogenic microorganisms like bacteria, virus, fungus, and protozoan parasites. These sulfated glycans belong to a variety of classes including glycosaminoglycans (GAGs) like chondroitin sulfate, fucosylated chondroitin sulfate, dermatan sulfate, unfractionated heparin, low-molecular-weight heparin, and acharan sulfate; and the less-famous algal polysaccharides known as sulfated fucans (including fucoidans), sulfated galactans (agarans and carrageenans), and sulfated heteropolysaccharides. Administration at certain concentrations of the antimicrobial sulfated glycans, especially those containing the higher amounts of the bioactive structural requirements, can lead to the interruption or disruption of the pathogen protein-host GAG complex formation, leading thus to the decrease or impairment of the microbial binding onto host cells. This report aims at presenting the current background concerning the therapeutic effects of the above-mentioned sulfated glycans as new antimicrobial agents. When sufficient data are available, discussion regarding structure-activity relationship is provided.
Keywords: Antifungal